2021
DOI: 10.1101/2021.09.05.459034
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rest/Stress Myocardial Perfusion Imaging by Positron Emission Tomography with 18F-Flurpiridaz: A Feasibility Study in Mice

Abstract: Background: Myocardial perfusion imaging by positron emission tomography (PET-MPI) is the current gold standard for quantification of myocardial blood flow. 18F-flurpiridaz was recently introduced as a valid alternative to currently used PET-MPI probes. Nonetheless, optimum scan duration and time interval for image analysis are currently unknown. Further, it is unclear whether rest/stress PET-MPI with 18F-flurpiridaz is feasible in mice. Methods: Rest/stress PET-MPI was performed with 18F-flurpiridaz (0.6-3.0… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…A volume of interest (VOI) delineating the myocardium was drawn manually by PMOD v.3.8 (PMOD Technologies, Switzerland). Average myocardial [ 18 F]flurpiridaz uptake from 20 to 40 min post injection, calculated from % injected dose per mL of the myocardium (% ID/mL), was used as a surrogate for myocardial perfusion at rest and following intravenous regadenoson injection, as previously reported [9]. Apparent coronary flow reserve (CFR App ) was calculated as the ratio between myocardial [ 18 F]flurpiridaz uptake following vasodilator stress and at resting conditions.…”
Section: Rest/stress Myocardial Perfusion Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…A volume of interest (VOI) delineating the myocardium was drawn manually by PMOD v.3.8 (PMOD Technologies, Switzerland). Average myocardial [ 18 F]flurpiridaz uptake from 20 to 40 min post injection, calculated from % injected dose per mL of the myocardium (% ID/mL), was used as a surrogate for myocardial perfusion at rest and following intravenous regadenoson injection, as previously reported [9]. Apparent coronary flow reserve (CFR App ) was calculated as the ratio between myocardial [ 18 F]flurpiridaz uptake following vasodilator stress and at resting conditions.…”
Section: Rest/stress Myocardial Perfusion Imagingmentioning
confidence: 99%
“…Apparent coronary flow reserve (CFR App ) was calculated as the ratio between myocardial [ 18 F]flurpiridaz uptake following vasodilator stress and at resting conditions. The term "apparent" is used because CFR App values were calculated without an arterial input function [9].…”
Section: Rest/stress Myocardial Perfusion Imagingmentioning
confidence: 99%
“…46,47 Novel promising tracers, such as 18 F-Flurpiridaz, may facilitate cardiac PET studies, since it has high image contrast in the myocardium, prolonged retention, superior extraction, relatively long half-life, which allows treadmill exercise regimen, so cardiac PET imaging could be performed without cyclotron on site. [20][21][22] Estimation of the absolute blood flow with 18 F-Flurpiridaz can be done by using simplified analysis of retention and SUV, due to superior imaging characteristics with promising results of improved quantitative accuracy, with techniques, which enable eliminating cardiac and patient motion and high diagnostic accuracy. 20,21 New multicentric studies should evaluate new therapy approaches in MVD and therapy evaluation with PET/CT.…”
Section: Pet Myocardial Imagingmentioning
confidence: 99%
“…[20][21][22] Estimation of the absolute blood flow with 18 F-Flurpiridaz can be done by using simplified analysis of retention and SUV, due to superior imaging characteristics with promising results of improved quantitative accuracy, with techniques, which enable eliminating cardiac and patient motion and high diagnostic accuracy. 20,21 New multicentric studies should evaluate new therapy approaches in MVD and therapy evaluation with PET/CT. Recent studies have showed that symptomatic patients with MVD and no coronary artery disease can have benefit from ranolazine since PET/CT CFR shows improvement after 30 days.…”
Section: Pet Myocardial Imagingmentioning
confidence: 99%
See 1 more Smart Citation